"I’M ON THE WAY...ALWAYS ON THE WAY..." - Sevrasevych, M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Diaries are common in literary circulation. As a rule, they are published after the death of the writer, which means that the choice of material, arrangement and composition depends on the person who undertakes this work. As a rule, this is a wife (as in the case of Oles Honchar’s diaries), or a compiler under the control of the family (as in the case of Stepan Pushyk’s diaries), or children (as in the case of Ivan Chendey’s diaries). That is, the diaries of the classics of Ukrainian literature of the second half of the 20th century are subject to family censorship. The author’s version of diaries, especially when it is internally oriented to be read by others (such as Roman Ivanychuk’s diaries), also has its drawbacks, the main of which is hidden or undisguised self-indulgence and passing all events through the prism of one’s own self.